Catalytic Oxidations in Organic Synthesis. Science of Synthesis, Workbench Edition Herausgegeben von Kilian Muniz. (20th November 2019) - Nachtsheim, Boris J.
Abstract : Thieme, 2018. 880 S., Broschur, 259.99 €.—ISBN 9783132012417